Reading ads, reading the world - Parry, Becky (Taylor & Francis, 2015)
This paper challenges the reductive notion of children as ‘efferent' readers who learn to decode written language in order to ‘take away’ knowledge. This anachronistic idea has become entrenched in current UK curriculum and education policy. However, it is well established that decoding letters and sounds is only one aspect of reading, that reading is cultural and that learning to read, not only words but also images and sounds, develops children's comprehension and criticality. With this in mind, I seek to share a process through which children and young people were able to develop as readers with a particular focus on the reading of media texts. I present an account of media education activity which focused on the way children read media texts, in the classroom. I suggest that with appropriate pedagogic and conceptual tools children develop as critical, cultural and collaborative readers of words, images, sounds and texts and thereby of the world.